Effect of Heat Stress on Thermoregulatory Response of Murrah and Nili Ravi Buffaloes in the Subtropical Region of India - Gupta, Deesha; Narang, Raman; Desmukh, Bharti; Malhotra, Puneet; Narang, Deepti (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Present study was conducted on the effects of thermal stress on adult Murrah and Nili- Ravi buffaloes (n=96). Using the temperature humidity index (THI), the thermal stress was calculated. THI was significantly (P<0.01) different for respiration rate (RR) and rectal temperature (RT). Parity was found to be non-significant. The overall mean values for morning respiration rate (MRR), noon respiration rate (NRR), morning rectal temperature (MRT), and noon rectal temperature (NRT) were 18.86 ± 0.51 breaths/min, 23.55 ± 0.61 breaths/ min, 100.29 ± 0.13 °F, and 100.50 ± 0.17 °F, respectively. Both season (P < 0.01) and breed (P < 0.05) had a significant effect on MRT. In contrast, only season had a significant effect on NRT. Significant effect of both breed and season (P < 0.01) was observed on morning respiration rate (MRR), whereas at noon, only season had a significant effect on noon respiration rate (NRR) (P < 0.01). Least squares means showed higher MRR (19.37 ± 0.51 breaths/min) and MRT (100.38 ± 0.13 °F) in Nili-Ravi buffaloes compared to Murrah buffaloes (MRR: 18.36 ± 0.52; MRT: 100.21 ± 0.13 °F). Murrah buffalo was found to be better thermotolerant than Nili Ravi buffaloes. Further validation in large population is required.